Sustainable development: twofold solidarity in the world of today and tomorrow - Gouzée, Nadine (Brussels, 2012)
"In the run-up to the Rio+20 Conference (20-22 June 2012) the state of play as regards sustainable development (SD) has little to show in terms of progress since the ‘Earth Summit’ held, also in Rio de Janeiro, twenty years ago. Nadine Gouzée stresses that the compartmentalization of efforts at all levels – which the critics refer to as ‘silo thinking – is the principal obstacle to achievement of an integrated form of development. The aim of Rio+20 is to revive the international community’s commitment to SD, focusing on the specific challenges represented by the green economy, by the need to improve world governance and by the new concept of Sustainable Development Goals. Only the presence of a strong social dimension to SD, with emphasis on the need for decent jobs and adequate social protection, can offer protection against the risks of injustice inherent in the transition to a green economy. "